Prosodic and Rhyme Patterns in Hafiz Ibrahim’s Poem "Ila Shadaqihi Muhammad ‘Abdihi Al-Babiliy Bika Yu’atibuhu": A Study of Neo-Classical Arabic Poem - Ilva Nurlatifah; Rohanda Rohanda; Muhammad Abdul Halim (Indonesian Journal of Arabic Studies, 2025)
Purpose—This study aims to analyze the prosodic and rhyme patterns in Hafiz Ibrahim’s poem "Ila Shadaqihi Muhammad ‘Abdihi Al-Babiliy Bika Yu’atibuhu," a representative work of the neoclassical school in Arabic poetry. The focus is on how traditional Arabic metrics and rhyme schemes are preserved and function within a modern emotional context. Design/methods/approach— The study employs a descriptive-analytic method and applies the theoretical framework of ‘Arudl (Arabic prosody) and Qawafi (rhyme theory). The analysis focuses on identifying metrical feet, rhythmic variations, and rhyme consistency throughout the poem. Findings— The findings indicate that the poem utilizes bahar khafif with modifications such as zihaf khabn and ‘illat tasy’its, reflecting a structured yet expressive rhythm. The rhyme scheme follows the pattern of qafiyah muthlaqah mardufah wa maushulah bi mad, ending consistently with the letter mīm, thus forming a qaṣīdah mīmiyyah. These features showcase Hafiz Ibrahim’s fidelity to classical form while conveying deeply personal sentiments. Research Implications— This study highlights the continued relevance and adaptability of classical prosody in modern Arabic poetry. It contributes to Arabic literary criticism by providing a stylistic reading of Neo-classical poetry that bridges traditional structure with modern expression.